MANAJEMEN PENGELOLAAN SAMPAH BAHAN BERBAHAYA DAN BERACUN (B3) RUMAH TANGGA DI MASA PANDEMIK COVID-19: SEBUAH TINJAUAN LITERATUR (Faletehan Jurnal Ekonomi dan Bisnis, 2023)
This study aims to describe the management of Household Hazardous Waste (HHW) during the Covid-19 pandemic. This study uses a descriptive with qualitative method. The results of the research show that Household Hazardous Waste (HHW) in Indonesia is not yet optimal. The low level of public awareness and concern causes the generation of household hazardous waste mixed with non HHW. Thus, the community mixes the two types of waste when it is disposed of. The accumulation of mixed HHW continues and ends up piling up in the Final Processing Site (TPA). It takes the role and responsibility of the government and public awareness in the management of household hazardous waste.